2021
DOI: 10.52472/jci.v4i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Aggressive Behavior Among Motorcycle Drivers and Its Relationship With Dangerous Driving Index in the State of Penang

Abstract: This study aims to identify the factors of aggressive behavior among motorcyclists in the state of Penang. Also identify the relationship between aggressive behavior factors and the dangerous driving index. This study is quantitative in nature by distributing questionnaires to 140 individuals who have been convicted under Section 42 (1) of the Road Transport Act 1987. Descriptive and inferential analysis methods are used to answer the research questions. Independent sample t-tests and one-way Anova were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Accelerometers [21][22][23], on-board diagnostics (OBD) [24], GPS sensing [25,26], gyroscopes [24,25], and ProLaser-III with motorcycles [27] have all been used in research studies related to road accidents. Despite the many disadvantages of the devices, they at least offer a complete record regarding day-to-day driving [11]. Even though the quantity of real-time driving studies (as research using this technology is identified) is restricted because of the resources and expenses required, they are becoming more frequent [28].…”
Section: Related Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Accelerometers [21][22][23], on-board diagnostics (OBD) [24], GPS sensing [25,26], gyroscopes [24,25], and ProLaser-III with motorcycles [27] have all been used in research studies related to road accidents. Despite the many disadvantages of the devices, they at least offer a complete record regarding day-to-day driving [11]. Even though the quantity of real-time driving studies (as research using this technology is identified) is restricted because of the resources and expenses required, they are becoming more frequent [28].…”
Section: Related Studiesmentioning
confidence: 99%
“…Normal driving behavior, also called "typical" or "safe" driving, refers to a driver's behavior when the driver avoids unsafe activities and reactions [11]. Normal driving style is defined as driving with no dangerous behaviors and without the qualities listed in aggressive driving, careless driving, alcoholic driving, and drowsy driving [34].…”
Section: Normal Driving Stylementioning
confidence: 99%
See 3 more Smart Citations